2013
DOI: 10.1126/science.1242592
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Ctenophore Mnemiopsis leidyi and Its Implications for Cell Type Evolution

Abstract: An understanding of ctenophore biology is critical for reconstructing events that occurred early in animal evolution. Towards this goal, we have sequenced, assembled, and annotated the genome of the ctenophore Mnemiopsis leidyi. Our phylogenomic analyses of both amino acid positions and gene content suggests that ctenophores rather than sponges are the sister lineage to all other animals. Mnemiopsis lacks many of the genes found in bilaterian mesodermal cell types, suggesting that these cell types evolved inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
851
6
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(905 citation statements)
references
References 49 publications
26
851
6
5
Order By: Relevance
“…We analyzed three main datasets from the original Mnemiopsis leidyi genome study (4). One dataset (Ryan-Choano) included only Choanoflagellata (the closest living relatives of Metazoa) as the outgroup.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed three main datasets from the original Mnemiopsis leidyi genome study (4). One dataset (Ryan-Choano) included only Choanoflagellata (the closest living relatives of Metazoa) as the outgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Another included Choanoflagellata plus more distantly related holozoans (Ryan-Holo), and the third (Ryan-Opistho) further included several Fungi (the most distantly related group to Metazoa among Opisthokonta). Applying the site-homogeneous general time reversible (GTR) substitution model (42), Ryan et al (4) found strong support for Ctenophora-sister in their analyses of all three datasets, and therefore concluded it is robust to outgroup composition. Ryan et al (4) also attempted to analyze these datasets using the site-heterogeneous CAT ("CATegory") model (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to resolve these relationships more clearly, an analysis based on genomic data was carried out. Phylogenomic analyses that used omics data have generally improved the robustness of molecular phylogenetic reconstructions and untangled many previously debated phylogenies among major eukaryotic lineages (Chiari et al, 2012;Hampl et al, 2009;Liang et al, 2013;Philippe et al, 2009;Philippe et al, 2005;Philippe and Telford, 2006;Ryan et al, 2013;Struck and Fisse, 2008). With respect to the phylum Ciliophora, the first phylogenomic analysis was carried out to explore the phylogenetic position of the ambiguous taxon Protocruzia (Gentekaki et al, 2014).…”
Section: / 25mentioning
confidence: 99%
“…Nextgeneration sequencing (NGS) now enables us to generate large data sets for many species at a relatively low cost. The systematic community has necessarily progressed from candidate genes through EST-based methods to 454 and Illumina-based transcriptome and genome datasets to resolve major relationships among the animal phyla (e.g., Dunn et al, 2008;Hejnol et al, 2009;Nosenko et al, 2013;Ryan et al, 2013;Moroz et al, 2014). Long outstanding issues have been resolved for within-phylum relationships among arthropods, molluscs, and annelids, to mention just some of the largest animal phyla (e.g., Meusemann et al, 2010;Kocot et al, 2011;Smith et al, 2011;Struck et al, 2011;von Reumont et al, 2012;Andrade et al, 2014;Weigert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%